Correlation between self-compassion and burnout among mental health workers - Georgievska, Anastasija; Naumovska, Andromahi (My University, 2023)
Burnout's impact on healthcare professionals has sparked concern for individuals and the healthcare system. This study examines the link between self-compassion and burnout in Macedonian mental health care professionals. Using a cross¬sectional design, data from 77 participants were analyzed through the Self¬Compassion Scale (SCS) and Maslach Burnout Inventory (MBI). The literature review underscores burnout's prevalence and introduces self¬compassion as a protective element. Objectives include understanding the relationship, gender/profession differences, and implications for healthcare. Results reveal significant correlations between self-compassion dimensions and burnout components. Higher self-compassion relates to lower burnout and depersonalization, while negative self-compassion aspects correlate with higher burnout. Though offering empirical insight, this study acknowledges limitations, such as its design and sample size. It recommends longitudinal studies and broader samples for future research. In conclusion, this research highlights self¬compassion's role in combating burnout and suggests interventions to bolster professional well-being. As the mental health field evolves, the study encourages further exploration of burnout and effective mitigation strategies.
Keywords: burnout; self-compassion; mental healthcare professionals; well-being